2020
DOI: 10.1177/2167696820969464
|View full text |Cite
|
Sign up to set email alerts
|

Identity Development During Student Exchange: A Qualitative Study of Students’ Perspectives on the Processes of Change

Abstract: Student exchange is associated with many positive outcomes, however, little is known about the experiences that drive such changes. The aim of the current qualitative study was to explore how exchange students conceptualize the processes of change and development during exchange within an identity framework. Twenty interviews were conducted with Australian and French exchange alumni aged 19–23 years. Thematic analysis identified two major themes of change with specific associated driving experiences titled “ I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 71 publications
0
9
0
1
Order By: Relevance
“…Several positive impacts received by the participants' are; the development of foreign language competencies, improved self-confidence (Marciniak & Winnicki, 2019), the emergence of a sense of independence, a sense of responsibility through decisions made or behavior (Attaalla, 2020), changes in priorities in the future, and intercultural understanding (McKay et al, 2020). From the results of the interview data, it is found that all the informants experienced an improvement in foreign languages competencies, most importantly in the English language.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several positive impacts received by the participants' are; the development of foreign language competencies, improved self-confidence (Marciniak & Winnicki, 2019), the emergence of a sense of independence, a sense of responsibility through decisions made or behavior (Attaalla, 2020), changes in priorities in the future, and intercultural understanding (McKay et al, 2020). From the results of the interview data, it is found that all the informants experienced an improvement in foreign languages competencies, most importantly in the English language.…”
Section: Resultsmentioning
confidence: 99%
“…There are various merits provided from students exchange programs, and some have a long-term impact on the participants, some of which are; increasing self-confidence (Marciniak & Winnicki, 2019), the emergence of a sense of independence (Atalar, 2020), and priority changes in the future (McKay et al, 2020). The development of participants' self-confidence can arise because of the experience of adjusting to a new and different environment and challenging participants to exceed their capabilities during student exchange programs (McKay et al, 2020). It is found that completing exchange program activities have become an achievement that the informants were proud of and encouraged the resource persons' self-confidence.…”
Section: Self-confidencementioning
confidence: 99%
See 1 more Smart Citation
“…Program pertukaran mahasiswa ke luar negeri membawa banyak perubahan positif. Namun, hanya sedikit pengalaman saat mengikuti program yang diangkat dalam bentuk penelitian ilmiah agar menjadi dorongan bagi mahasiswa lain mengambil manfaat dari perubahan tersebut (McKay, Lannegrand, Skues, & Wise, 2020). Pertukaran mahasiswa biasanya adalah program yang mengharuskan mahasiswa menyelesaikan satu atau dua semester di perguruan tinggi mitra di luar negeri sebagai bagian dari pemenuhan syarat untuk memperoleh gelar mereka (Engle & Engle, 2003).…”
Section: A Pendahuluanunclassified
“…As identity development is widely believed to be an important process whilst learning in different cultural and academic contexts, it is rather noteworthy that quite limited use has been of theoretically informed analyses to explore ways in which college students' career identities are impacted by prior studies abroad (Jon et al. , 2020; McKay et al. , 2022; Norris and Gillespie, 2009).…”
Section: Introductionmentioning
confidence: 99%